ANALYSIS MODELS OF TEACHING PRACTICES - Bekhtaoui Djamal,; Mokrani Djamel,; Benzidane Houcine, (Sport Scientific And Practical Aspects, 2025)
The paper aims to demonstrate models of analysis of teaching practices in the classroom. It first explains the types of analysis of teaching practices and the challenges to their use. Then, it provides a detailed examination and commentary on each model,The paper comes to the conclusion that the Clazer model is a simplified representation of the teaching practice, as it reflects the characteristics of the model, which are reduction and concentration. Besides, it highlights the necessary components of the model, and connects them through a mediator, which is the feedback.